Genomic methylation patterns in pre-meiotic gynoecia of wild-type and RdDM mutants of Arabidopsis - Ortiz-Vasquez, Quetzely; León-Martínez, Gloria; Barragán-Rosillo, Carlos; González-Orozco, Eduardo; Deans, Samuel; Aldridge, Billy; Vickers, Martin; Feng, Xiaoqi; Vielle-Calzada, Jean-Philippe (Frontiers in Plant Science, 2023)
Although DNA methylation patterns are generally considered to be faithfully inherited in Arabidopsis thaliana (Arabidopsis), there is evidence of reprogramming during both male and female gametogenesis. The gynoecium is the floral reproductive organ from which the ovules develop and generate meiotically derived cells that give rise to the female gametophyte. It is not known whether the gynoecium can condition genomic methylation in the ovule or the developing female gametophyte. We performed whole genome bisulfite sequencing to characterize the methylation patterns that prevail in the genomic DNA of pre-meiotic gynoecia of wild-type and three mutants defective in genes of the RNA-directed DNA methylation pathway (RdDM): ARGONAUTE4 (AGO4), ARGONAUTE9 (AGO9), and RNA-DEPENDENT RNA POLYMERASE6 (RDR6). By globally analyzing transposable elements (TEs) and genes located across the Arabidopsis genome, we show that DNA methylation levels are similar to those of gametophytic cells rather than those of sporophytic organs such as seedlings and rosette leaves. We show that none of the mutations completely abolishes RdDM, suggesting strong redundancy within the methylation pathways. Among all, ago4 mutation has the strongest effect on RdDM, causing more CHH hypomethylation than ago9 and rdr6. We identify 22 genes whose DNA methylation is significantly reduced in ago4, ago9 and rdr6 mutants, revealing potential targets regulated by the epigenetic landscape in premeiotic gyneocia. Our results indicate that drastic changes in methylation levels in all three contexts occur in female reproductive organs at the sporophytic level, prior to the alternation of generations within the ovule primordium, offering a possibility to start identifying the function of specific genes acting in the establishment of the female gametophytic phase of the Arabidopsis life cycle.